Family Participation in Postnatal Oxytocin Massage During Covid-19 Pandemic - Prasetya Lestari; Fatimah Fatimah (Alma Ata University Press, 2020)
In 2019, the coverage of breastfeeding in Indonesia has yet to reach the target set by the government. The low coverage of exclusive breastfeeding will harm the baby, mother, family as well as the country. Rawat, et al (2018) stated that one of the causes which lead to the breastfeeding failure in the primiparous first week of childbirth is that the mother finds it difficult to get a proper breastfeeding latch and feels that her breast milk is not sufficient. Another study conducted by Jacobs, et al. proved that the majority of respondents felt that their milk production was low, so they decided to provide complementary milk. Oxytocin massage has shown to increase relaxation, induce more comfortable and high-quality sleep, reduce pain and stress and help to increase the oxytocin and prolactin hormone. This study aims to determine the family's participation in postnatal oxytocin massage during the COVID-19 pandemic and is categorized as a descriptive observational research. For this purpose, 70 postnatal mothers from Maternal and Child Health Centers and Independent Midwife located in Bantul, Sleman, and Gunung Kidul were taken as respondents. The data were collected from May until September 2020. The samples taken were family and postnatal women from the first day postnatal until third day who then were evaluated for up to 1 week. The results showed that family’s participation in conducting the oxytocin massage was mostly carried out by the husbands (91.4%). However, other family members were also recorded to participate including biological mothers (2.9%), mother-in-law (1.4%), and the participants’ sisters (4.3%). Thus, we can conclude that husband's participation is very important in giving postpanatal oxytocin massage during COVID-19 pandemic.